Nimbus BUV (1967)
Designed for use on the Nimbus 4 weather satellite, the Backscatter Ultraviolet Instrument (BUV) measured the ozone distribution in the atmosphere.
Keywords: Atmospheric ozone; Photoelectric multipliers; Scientific apparatus and instruments; Monochromator; Nimbus (Artificial satellite); Atmospheric ozone--Measurement; Beckman Instruments, Inc.; Ultraviolet radiation